2010
DOI: 10.1038/jp.2010.20
|View full text |Cite|
|
Sign up to set email alerts
|

Poractant alfa and beractant treatment of very premature infants with respiratory distress syndrome

Abstract: Objective: Comparison of the differences between availability of animalderived surfactant preparations used to treat premature infants is incomplete. The objective of this study was to assess the short-term treatment efficacy of the two most commonly used surfactant preparations in the United States, beractant (100 mg kg Result: We studied 52 infants 24 0/7 to 29 6/7 weeks gestation; 25 received poractant alfa (27.1±1.6 weeks, birth weight of 930±231 g) and 27 received beractant (26.7 ± 1.7 weeks, P ¼ 0.343 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 16 publications
3
41
1
2
Order By: Relevance
“…More infants in the poractant alfa group were extubated at 48 and 72 h (*P<0.05). (6). Thus, there was a difference in the PDA management and hemodynamics in infants treated with poractant alfa, compared with beractant that was associated with improvement in respiratory status.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More infants in the poractant alfa group were extubated at 48 and 72 h (*P<0.05). (6). Thus, there was a difference in the PDA management and hemodynamics in infants treated with poractant alfa, compared with beractant that was associated with improvement in respiratory status.…”
Section: Resultsmentioning
confidence: 99%
“…These differences were associated with a more rapid and sustained improvement in respiratory function in the poractant alfa group, allowing more elective extubations at 48 and 72 h than in the beractant group. 6 We did not demonstrate a direct surfactant effect on PDA closure or PDA hemodynamics by echocardiographic evaluation following the second dose of poractant alfa or beractant. Since PDAs tended to be treated earlier in the poractant alpha group, yet there were more PDAs treated in the beractant group, it is unlikely that early treatment of PDAs that would have close spontaneously, accounted for the lower number of PDAs treated in the poractant alfa group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Faster weaning of oxygen and mean airway pressure was reported with CA compared to BE, and no differences in the need for additional doses, mortality or any other clinical outcomes were seen [84,85]. In contrast, comparison of porcine surfactant PA, with bovine surfactant BE from 6 randomized trials, showed faster weaning of oxygen, faster weaning of PIP and mean airway pressure, fewer air leaks, less need for additional doses, less patent ductus arteriosus, less patients on invasive ventilation after 72 hours, and decreased the incidence of BPD and also reduced mortality [86][87][88][89][90][91]. Clark et al [92] reported no difference in mortality between BE and CA in a retrospective study of 5,169 patients.…”
Section: Clinical Comparison Of Animal Derived Surfactantsmentioning
confidence: 99%
“…No se logró demostrar diferencias para los otros parámetros de ventilación y de oxigenación. Otros autores, demostraron diferencias significativas en la presión media de la vía aérea favoreciendo al poractant alfa al compararlo con beractant 10,11 , la cual fue menor entre las primeras 24-72 h. Singh N y cols. 6 , informan en su meta-análisis una disminución de los requerimientos de O 2 para el poractant alfa a 200 mg/kg cuando se le comparó con beractant 100 mg/kg.…”
Section: Americana De Pediatría Y Los Lineamientos Del Consenso Europunclassified